How to be acquired by Google?: Analysis of target firms acquired by Google Inc. - Soojung Yeon (International Telecommunications Society (ITS), 2018)
Many technological and digital entrepreneurship called 'start-ups' are being established and gone out of business in the market. There are various routes for start-up success and being acquired by other company is a major option for them as an exit strategy. The purpose of this study is to find out the characteristics of firms which succeed in exit by acquisition. To do so, this study selected Google and analyzed 178 completed acquisitions of Google via two-step cluster analysis using variables drawn from a literature review. The two-step cluster analysis resulted in five clusters among Google's acquisitions. The different characteristics among each cluster are explained and the implication of the study is presented.
Keywords: 330; Acquisition; Exit strategy; Startup; Google; Two-step cluster analysis